An incidence study of diagnosed autism‐spectrum disorders among immigrants to the Netherlands. (9th December 2012) - van der, E.; Termorshuizen, F.; Laan, W.; Breetvelt, E. J.; van, J.; Selten, J. P.
<x xml:space="preserve">Abstract</x> Objective To estimate the risk of developing autism‐spectrum disorder (ASD) in children born to immigrants as compared with children of Dutch‐born parents. Method Retrospective, population‐based cohort study of all live births (n = 106 953) between 1998 and 2007 in a circumscribed geographical region in the Netherlands. Cohort members were linked to the Psychiatric Case Register to identify diagnosed cases. Results A total of 518 cases of ASD were identified, including 150 children with autism and 368 children with Asperger syndrome or Pervasive Developmental Disorder Not Otherwise Specified (PDD‐NOS). Children born to migrants from developing countries were at significantly lower risk of ASD [rate ratio (RR) = 0.6, 95% confidence interval (CI) 0.5–0.9] than children of Dutch‐born parents. Within the ASD group, the risk for the subgroup with Asperger syndrome and PDD‐NOS was reduced (RR = 0.4, 95% CI 0.3–0.6), whereas that for narrowly defined autism was non‐significantly increased (RR = 1.4, 95% CI 0.9–2.4). Migrant groups did not differ in age at diagnosis. Conclusion The results echo Swedish findings indicating a reversal of risk gradient in children of parents from developing countries, specifically a decreased risk for high‐functioning and increased risk for low‐functioning autism.